Meningkatkan Imajinasi Sejarah melalui Penggunaan Novel dalam Pembelajaran Sejarah - Ira Septiansi; Nana Supriatna; Wildan Insan Fauzi (Universitas Hamzanwadi, 2025)
This study aims to examine the influence of using the historical novel Kurir-Kurir Kemerdekaan as a learning source on high school students’ historical imagination. Historical imagination includes the ability to re-enact past events, interpret their meaning reflectively, and understand the emotions and motivations of historical actors within their temporal context. A quasi-experimental design with a non-equivalent pretest–posttest group approach was employed. Two classes participated: the experimental group, which used a historical novel, and the control group, which engaged in a project-based shadow puppet performance. Results showed that the experimental group experienced a statistically significant improvement (p < 0.001), from an average score of 25.42 to 52.33, with an N-Gain of 35.56, higher than the control group’s 22.86. Indicator-based analysis revealed the highest gain in empathy (0.39), followed by interpretation (interrogation) at 0.28, and narrative reconstruction (re-enacting) at 0.24. These findings demonstrate that historical novel-based instruction is more effective in enhancing students’ affective and reflective engagement with history. The narrative elements within novels help students form emotional and cognitive connections with the past and interpret historical events in a more humanistic manner.